Electronic nicotine delivery systems: Adult use and awareness of the 'e-cigarette' in the USA - Regan, Annette; Promoff, G.; Dube, S.; Arrazola, R. (BMJ Publishing Group, 2013)
Background Electronic nicotine delivery systems (ENDS), also referred to as electronic cigarettes or e-cigarettes, were introduced into the US market in 2007. Despite concerns regarding the long-term health impact of this product, there is little known about awareness and use of ENDS among adults in the USA. Methods A consumer-based mail-in survey (ConsumerStyles) was completed by 10 587 adults (=18 years) in 2009 and 10 328 adults in 2010. Data from these surveys were used to monitor awareness, ever use and past month use of ENDS from 2009 to 2010 and to assess demographic characteristics and tobacco use of ENDS users. Results In this US sample, awareness of ENDS doubled from 16.4% in 2009 to 32.2% in 2010 and ever use more than quadrupled from 2009 (0.6%) to 2010 (2.7%). Ever use of ENDS was most common among women and those with lower education, although these were not the groups who had heard of ENDS most often. Current smokers and tobacco users were most likely to try ENDS. However, current smokers who had tried ENDS did not say they planned to quit smoking more often than smokers who had never tried them. Conclusions Given the large increase in awareness and ever use of ENDS during this 1-year period and the unknown impact of ENDS use on cigarette smoking behaviours and long-term health, continued monitoring of these products is needed.